(untitled) (Economic and Political Thought, 2023)
The article assesses the threats caused by the Chinese Belt and Road Initiative (BRI) for Poland’s economic security in 2015–2023. A literature review on the Belt and Road Initiative (BRI) was used, as well as an analysis of available data, expert knowledge resulting from investment projects completed in Poland under IPS, the author’s previous publications on this topic, and the author’s professional experience in projects in one of the Chinese companies— technology in the Central and Eastern European region. The article aims to answer the question of whether the Chinese Belt and Road initiative threatens Poland’s economic security. The added value of the article is the analysis of the impact of the Belt and Road Initiative on Poland’s economic development as part of changes in the functioning of the European Union. The author refers to Modliński’s theory of hegemonic cycles to answer the question and also discusses the possibilities of alternative solutions to the Chinese Belt and Road Initiative. The research gap is the issue of assessing the threat to Poland’s economic security in connection with the implemented BRI initiative.